MANAGEMENT OF RELIGIOUS EDUCATION PROGRAMME DEVELOPMENT FOR MUSLIM MINORITY COMMUNITY IN MADRASAH ANDALUS SINGAPORE - Rosad, Ade; Sirozi, M.; Karoma, Karoma (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study was conducted because the management of the development of access to Islamic religious education in the Andalus Singapore Half-Time Madrasah presents new ideas and breakthroughs that are relevant to be used as a reference for educational practitioners. Research Objectives: To provide information to the reading public about the management strategy of developing access to Islamic religious education at the Half-Time Andalus Madrasah in Singapore.Method: This research uses descriptive qualitative method to examine the phenomenon in depth through field data analysis and documentation. Results: The research shows that quality-oriented management that is responsive to the needs of the community can be used as a model in encouraging innovation in Islamic education institutions, both formal and non-formal. This approach has proven effective in designing programmes that are relevant to the needs of learners. Conclusion: Although this study has limitations such as the lack of interviewees, data that only focuses on educational programmes, and the lack of information outside the official Andalus website, the findings still make an important contribution. The Andalus management model can be adapted by Islamic education institutions in similar contexts, especially in improving access, relevance and quality of religious education programmes by tailoring curricula and education services to the needs of learners and the surrounding community.